P3.018 Development of a C. Trachomatis-Specific Competitive Pgp3 ELISA. (13th July 2013) - Wills, G; Samuel, D; Warrener, L; Horner, P; McClure, M
Abstract : Background: Chlamydia trachomatis (CT) DNA testing of genital samples principally from symptomatic persons provides information about active infection only, and is unlikely to represent true prevalence of current and past infection in the population. Serological tests applied to serum collections that are more representative of the general population can help understanding the pattern of the infection. We previously described an indirect immunoglobulin G (IgG) enzyme-linked immunosorbent assay (ELISA) based on the CT-specific antigen Pgp3. Sensitivity and specificity were determined using ROC curve analysis of data from 356 sera from CT-infected patients and 722 paediatric sera. The assay works particularly well in women, with a greater sensitivity (74%) than commercial assays (60%), and is suitable for use in seroprevalence studies. However, there is a need to confirm the specificity of samples reactive in the indirect Pgp3 ELISA and, to this end, we have developed a competitive Pgp3 ELISA. Methods: Purified IgG from human sera containing high titre antibody to CT was labelled with HRP and, by optimising conditions and using chequerboard titrations, an assay developed where test sera compete with labelled IgG for epitopes on the Pgp3 protein. Results: The competitive assay was optimised, then 89 sera from our CT-infected patient cohort (patients having had at least one positive CT NAAT result at least one month previously) and 91 paediatric sera were assayed by both the indirect and competitive Pgp3 ELISAs. Results by these two assays were concordant. Conclusion: A competitive ELISA based on the CT-specific Pgp3 protein has been developed, which confirms the specificity of the indirect Pgp3 ELISA.